A U.S. based survey of loan burden among anesthesia trainees and its impact on well-being - Pawar, Niti; Boscardin, Christy K.; Chen, David; Earnest, Gillian; Barreto Chang, Odmara L. (Frontiers in Education, 2025)
IntroductionLoan burden presents a significant barrier for trainees in different medical fields. However, disparities in loan burden of anesthesia trainees of underrepresented in medicine (URiM), first-generation and female-identifying backgrounds have not been studied. Moreover, it is not known whether membership in these groups is associated with well-being or life decisions after controlling for loan burden.MethodsIn this cross-sectional observational study, an online survey was disseminated by the American Society of Anesthesiologists (ASA) to anesthesia trainees in the United States (U.S.) from October to November 2022. Demographic information, Harvard Mental Health Continuum-Short Form (MHC-SF) well-being scores, and whether trainees perceive loan burden as delaying buying a house or having children were all collected. We evaluated associations between demographic group memberships, probability of having high loan burden, and delayed life decisions and well-being before and after adjusting for high loan burden.ResultsThe study represents 952 of 6,502 U.S. trainees (14.6%). The respondents had a mean age of 31 years, and 385 identified as female (40.4%), 150 as URiM (15.8%), and 634 as first-generation college (FGC) trainees (66.6%). The proportion of trainees with high loan burden was higher in the URiM 138 (92.0%) and FGC groups 565 (89.1%). Trainees in the high loan burden group were more likely to delay having children (OR = 3.69, 95% Simultaneous Confidence Interval (SCI) 2.38–5.73) and delay buying a home (OR = 5.27, 95% SCI: 3.45–8.05). Once loan burden was adjusted for, many disparities persisted in associations: URiM delaying buying a home (OR = 2.14, 95% SCI: 1.01–4.54), FGC delaying buying a home (OR = 1.56, 95% SCI: 1.02–2.38), female-identifying delaying children (OR = 1.49, 95% SCI: 1.04–2.13) and female-identifying well-being (Diff = −3.47, 95% SCI: −5.83, −1.11).ConclusionsFGC and URiM anesthesia trainees have significantly higher odds of having high loan burden and continue to experience disparities in life decisions after controlling for loan burden. Female-identifying trainees have significantly higher odds of delaying childbearing and have lower well-being after controlling for loan burden.